(3GdeNJUQ ef NUGFU GdfHi Udi Gddg Ydjg hSdes - (3CHh GdQHjY SdjeGf Hf SHY GdSdejs
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdPi dGjJHYV ef GdCYOGO s
(3hgh YTQI CHhGH MPa ef Chdg CQHYI CHhGH hPdc GdPi GNJGQg eSJfSN GdcJGH aCLjH Edi Pdcs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B239 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs